2015
DOI: 10.1115/1.4031625
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tip Leakage Flow on the Performance of Multistage Compressors Used in Small Core Engine Applications

Abstract: Large rotor tip clearances and the associated tip leakage flows are known to have a significant effect on overall compressor performance. However, detailed experimental data reflecting these effects for a multistage compressor are limited in the open literature. As design trends lead to increased overall compressor pressure ratio for thermal efficiency benefits and increased bypass ratios for propulsive benefits, the rear stages of the high-pressure compressor will become physically small. Because rotor tip cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…It confirms the findings of Berdanier and Key [20] and add new information for tip clearances larger than / = 4%.…”
Section: Compressor Characteristicssupporting
confidence: 78%
See 2 more Smart Citations
“…It confirms the findings of Berdanier and Key [20] and add new information for tip clearances larger than / = 4%.…”
Section: Compressor Characteristicssupporting
confidence: 78%
“…The last tested tip clearance increase from / = 3.7% to 5.0% (TC3-4) in this paper, however, shows a remarkably different behavior because the stall mass flow is not increased but decreased and hence the derivative is −0.6. This behavior has not been detected by [1,20,21] because their largest tip clearance size is notably lower than the largest tested tip clearance size in this paper. Wisler et al [15] tested two compressors A and B with largest tip clearance sizes of / = 5.5% and / = 4.5%, Groove s/c = 1.2%  = 1.00…”
Section: Compressor Characteristicsmentioning
confidence: 69%
See 1 more Smart Citation
“…5 found that in multistage axial compressors, an increase of the radial tip clearance leads to a dramatic reduction of operability (by 20%), pressure ratio, and efficiency. Berdanier and Key 6,7 conducted a detailed experiment on a multistage axial compressor with different tip clearances and found tip clearance has different influences on different stages through its influence on tip leakage flow trajectories. A detailed investigation concerning the effect of tip clearance and blockage on the matching of multistage axial compressors as well as on the performance and stability was done by Domercq and Escuret, 8 and this was further validated by Yang et al.…”
Section: Introductionmentioning
confidence: 99%
“…As is well-known, tip clearance size (TCS) has a large impact on compressor performance and stability, and is therefore a crucial factor in turbomachinery aerodynamic design. 14 The influence that TCS exerts over the flow field of the blade tip region has been extensively studied for decades. The TCS of an engine may change because of many uncertainty factors such as varying thermal expansion, casing variations and eccentricity of rotor wheel in casing.…”
Section: Introductionmentioning
confidence: 99%